(untitled) (Vietnam Journal of Community Medicine, 2026)
Introduction and objective: COVID-19 mRNA vaccines have demonstrated high efficacy; however, rare adverse events such as myocarditis have increasingly been reported. This report describes two cases of myocarditis occurring after the first vaccine dose, a presentation that remains uncommon in the literature. Case presentation: Two previously healthy pediatric patients without underlying conditions presented with chest pain following mRNA vaccination. The first case had a moderate course with reduced ejection fraction (EF) and elevated cardiac enzymes, responding well to corticosteroid therapy. The second case presented with severe progression, including cardiogenic shock and complete atrioventricular block (third-degree AV block), requiring temporary pacing and vasopressor support. Intervention and outcomes: Both patients received intensive medical treatment, including corticosteroids and cardiovascular support. Cardiac function and laboratory parameters fully recovered following treatment. Conclusion: Myocarditis following mRNA COVID-19 vaccination is a rare but potentially severe adverse event, requiring close monitoring and timely management.